Topical glucocorticosteroids in the treatment of patients with allergic rhinitis - A. Yu. Ovchinnikov; N. A. Miroshnichenko; I. V. Smirnov (Медицинский совет, 2019)
Allergic rhinitis (AR) is a common disease that affects people regardless of age, place of residence or social status. As a rule, the allergen enters the body through the upper respiratory tract, the entrance gate is mainly the nasal mucous membrane. According to statistics, in recent years the frequency of perennial AR (PAR) in economically developed countries has been approaching 40-50%. In AR, inflammatory infiltration of the nasal mucous membrane by various cells is observed. Nowadays, AR is characterized by early onset, often with continuous relapsing course and resistance to antiallergic therapy. The study of the mechanisms of disease development creates the basis for rational therapy, which involves the impact on a complex inflammatory response, not only on the symptoms of allergy. Therefore, timely conservative therapy with intranasal topical glucocorticosteroid is advisable. The article shows the importance of the effectiveness of Flixonase intranasal spray in the treatment of AR. This drug may be recommended for the treatment of PAR. Studies of the use of the drug have shown a multi-purpose mechanism of its action. Flixonase significantly reduces the number of inflammatory cells in the nasal mucous membrane and inhibits the action of local inflammatory mediators in both seasonal ARs and PARs. To achieve the best results, the drug should be used at the first signs of nascent AR.